Modelling of the thermal condition on selective laser melting (SLM) of zirconia powders - Chen, Zhiyi (2014)
Selective Laser Melting (SLM) is an additive manufacturing technique capable of fabricating complex products layer by layer in a wide range of materials, particularly for metallic materials. As for ceramic materials such as Zirconia however, inconsistent part density continues to pose a challenge to the understanding of the relations between SLM process parameters and the aforementioned material. In this report, the thermal effect of SLM parameters on Zirconia are investigated numerically. A three dimensional transient thermal finite element model of the SLM process is presented. Temperature distribution simulation of a single-track laser melting with both Uniform and Gaussian laser beam profiles are conducted on a single-layered Zirconia powder bed model. The simulation results show that higher laser power and slower scanning speed yield a higher maximum temperature in the powder bed for both laser beam profiles. Gaussian laser beam, despite inducing higher laser energy due to its smaller laser